A note on involutions in Ore extensions (2017)
Skew-polynomial rings, or Ore extensions, constitute an important class in noncommutative ring theory. These structures are currently studied from different points of view such as ideal theory, order theory, Galois theory, homological algebras, etc. Computationally, Ore extensions appear in the context of uncoupling and solving systems of linear differential and difference equations in closed form. In this short note we let K denote a division ring, α: K $rarr; K a ring endomorphism and δ: K → K an α-derivation. We determine the involutions in the Ore extension K[x; α, δ].